'An Unnatural Crime': Infanticide in Early Nineteenth-Century Ireland. (December 2019) - Kelly, James
Infanticide reached record levels in Ireland in the mid-nineteenth century. Although the rising population and increasing poverty provided the essential precondition for this, the sharp rise in the practice identified by contemporaries in the 1820s and 1830s might not have taken place had the Dublin and Cork Foundling Hospitals continued to assume responsibility for the care of foundling children. But once they were no longer available to receive them, the women who give birth to the children that society identified as illegitimate chose to terminate their lives in record numbers in an attempt to avoid the severe stigma that this brought and the practical difficulties of taking care of a child alone. Using the cases that came before the coroners court and the crime figures assembled by the Royal Irish Constabulary from the 1830s, this article combines the quantitative analysis of the practice that this permits with a reliance on the qualitative approach that informed a previous investigation of the phenomenon in the eighteenth century to track its evolving trajectory, to identify its main features and to explain how it had arrived at a point by the 1840s when it exceeded homicide as the primary cause of violent death.